A Comparison of Different Shipment Policies in an Integrated Inventory System for Imperfect Quality Items with Inspection Errors. (24th September 2017) - Zhou, Yongwu; Zhang, Xiong; Lin, Zhaozhan
Abstract : Considering a production-ordering system where items are not perfect and quality screening is conducted with inspection errors, we develop integrated inventory models under different shipment policies and make a comprehensive comparison among them to select an optimal one, so as to improve the supply chain's performance. It is assumed that all items classified as defective during the screening process are sold as a single batch at a discounted price at the end of this screening process; items returned from the market are accumulating; and all of them are stored and sold as a single batch at a discounted price at the end of the next screening process. All the numerical results show that the proportional size shipment policy is always optimal, except for one situation where the difference between the vendor's and the buyer's unit inventory holding costs is considerably large. Therefore, we mainly recommend the proportional size shipment policy.